2000
DOI: 10.1046/j.1365-2842.2000.00488.x
|View full text |Cite
|
Sign up to set email alerts
|

Mandibular position at chin‐point guided closure, intercuspation and final deglutition in asymptomatic and temporomandibular dysfunction subjects

Abstract: This study compared the mandibular position at chin-point guided jaw closure, intercuspation and final deglutition (position at the end of swallowing) in 159 asymptomatic subjects and 142 subjects with symptoms in the craniomandibular system. The symptomatic subjects were assigned to four groups showing an adapted centric posture, pain, luxation with reduction of the temporomandibular joint and pain with luxation and reduction. Computer equipment aided recording of hinge axis movements in three dimensions. Whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 37 publications
1
3
0
1
Order By: Relevance
“…Therefore, this position is closer to MI and is more appropriate than the position obtained with the other evaluated methods. These results are in agreement with those of other studies (6,13).…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Therefore, this position is closer to MI and is more appropriate than the position obtained with the other evaluated methods. These results are in agreement with those of other studies (6,13).…”
Section: Discussionsupporting
confidence: 94%
“…The swallowing technique was largely commented and criticized by some authors for its great variability (7,13). Considering the results obtained in this study and reported in the literature (8), the use of an anterior jig has contributes to reduce this variation.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Otros estudios evalúan variaciones en la posición mandibular más que cambios a nivel condilar medidos con imágenes (3,7,9,10,(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25) . Por otro lado, la RC se define cuando el cóndilo mandibular está ubicado en la posición más anterior y superior de la ATM enfrentando vertiente posterior de la eminencia articular (4) .…”
Section: Discussionunclassified
“…Therefore, various methods were proposed, which could clinically determine a mandibular position for the ICP without depending on the condylar position, including the following methods; the speaking method [36] and the swallowing method [37], [38]. In addition, muscular position (MP) [39] defined as the horizontal contact position of the mandible by the reflex muscle pattern, acting as a terminal point of closing movement from the rest position [40], [41] can also be considered.…”
Section: Effectiveness Of Habitual Closing Movementsmentioning
confidence: 99%